Implementasi Google My Business sebagai Media Digital Marketing - Tsalis Kurniawan Husain; Alam Budiman Thamsi; Farizah Dhaifina Amran (Jurnal Pengabdian Masyarakat (abdira), 2022)
This community service activity involves a partner which engaged in micro, small and medium enterprises of brick making. Partner problems are the lack of knowledge and skills in marketing their products and the location of their business has not been registered digitally on the internet so that the business cannot be accessed by some potential customers. Problems in this target group need to be addressed by facilitating them in implementing Google My Business (GMB) as an easy and inexpensive digital marketing platform. The method used in this community service activity is participation and mentoring. The result of this activity is that the partner's business has been successfully registered and verified on Google Maps and GMB. The results of the GMB account performance show that during the last one month since it was implemented, the partner's business has been discovered 325 times by potential customers in the internet. This shows that the partner's GMB account has functioned well as a digital marketing platform. This activity also made a GMB-based business website and have been included in the partner's business profile so that their business looks more professional.